Rancang Bangun Sistem Informasi Akuntansi Berbasis Web Menggunakan Metode Waterfall - Febriani Sulistiyaningsih (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
The use of information systems and information technology today greatly facilitates and helps in daily work. The rise of MSMEs, CVs and Startups in various fields of expertise certainly have their own business financial records. However, most of the company's financial records are still manual, so an accounting or financial information system was designed to facilitate the company's financial records. The creation of this company's accounting or financial information system certainly has several stages that must be passed. The waterfall method, which is one of the software development methods, is used in the creation of this accounting or financial information system. This is because by using the waterfall method, each stage can be done easily and clearly. The results of this study in the form of a company's accounting or financial information system will certainly make it easier for companies to help record company finances.